Seasonal variation of endogenous adrenocorticotropic hormone concentrations in healthy non-geriatric donkeys in Northern California - Humphreys, Sarah; Kass, Philip H.; Magdesian, K. Gary; Goodrich, Erin; Berryhill, Emily (Frontiers in Veterinary Science, 2022)
Elevated plasma adrenocorticotropic hormone (ACTH) is often used to diagnose pituitary pars intermedia dysfunction (PPID) in horses. The hormone naturally increases in the fall in horses, and donkeys have been found to have higher ACTH concentrations than horses. However, circannual variation of ACTH has not been assessed in donkeys. The objective of the study was to establish seasonal variation of basal plasma ACTH concentrations over the course of a year in clinically healthy, non-geriatric donkeys. It was hypothesized that donkey ACTH concentrations would be higher than those reported in horses without PPID in all seasons, and that, similarly to horses, ACTH concentrations would further increase in the fall months. Twenty-six healthy adult donkeys (10 standards, 16 miniatures), a median (range) of 6 (2–13) years of age, were included. Donkeys were housed at a single location. Serial plasma samples were obtained monthly for 12 months. Plasma ACTH concentrations were determined by immunoassay. Data are presented as median (range), with a P-value < 0.05 considered significant. ACTH concentrations were lowest in the winter and spring [12.8 (5.0–73.6) pg/ml and 12.5 (2.8–62.6) pg/ml, respectively], with an increase in the summer [53.2 (29.7–305.0) pg/ml], and peak in the fall [77.1 (12.4–319.0) pg/ml]. ACTH concentrations were highest in the month of September [122.0 (41.7–319.0) pg/ml]. Donkey ACTH concentrations were higher than equine reference ranges from May through November but showed similar circannual variation with dramatic increases in the fall months. Species-specific reference ranges are necessary for accurate interpretation of endocrinopathy screenings in donkeys.